A new domain‐based implicit‐explicit time stepping scheme based on the class of exponential integrators called sEPIRK. Issue 1 (18th November 2019) - Straub, Veronika; Ortleb, Sigrun; Birken, Philipp; Meister, Andreas
Abstract: Reliable simulations of flows in real applications involve the task of discretizing both space and time in an accurate and efficient way. To cope with the large semidiscrete systems resulting from a space discretization on appropriate grids, which often include comparatively few very small cells near solid walls for boundary layer resolution, an implicit‐explicit time stepping scheme can be the most efficient variant. We present such a type of scheme utilizing recent exponential integrators called sEPIRK and show its computational advantages opposed to IMEX‐Runge‐Kutta schemes.